A organização administrativo-burocrática da instrução pública paulista: estudo sobre o regulamento da diretoria geral de 1910 - Paulo, Marco Antonio Rodrigues (2007)
The objective of this thesis is to analyze the bureaucratic/administrative structure of the public schools, starting with the General Directory´s regulation of 1910. The range extends up until the year 1919, which precedes the Sampaio Dória Reforms. Two movements are realized: the first consists of comparing the bureaucratic/administrative structure implanted by the regulations of public instruction of 1893 and 1898, with the regulation that created the General Directory of Public Instruction in 1910. For this, two categories of analysis are considered: government offices- the structure that administrates and inspects public instruction in the state of São Paulo, and the category of public post- the criteria established for the recruitment and standards for the posts of General Director of public studies and School Inspector. The second movement consists of a comprehensive understanding of the Paulista school structure, from a qualitative and from a quantitative perspective. In terms of the qualitative aspect, the reports from public school employees who occupied a position of General Director or School Inspector were analyzed in relation to their the evaluation of the Paulista public school system as a whole during the period considered in this project. In relation to the quantitative aspect, school statistics and public resources destined for school maintenance were analyzed, as well as the expansion of the Paulista public school system. The most important source of information related to this topic comes from the state of São Paulo yearly Teaching Reports. This study confirms, first, that the process of the rationalization and the bureaucratization instituted at the administration of Paulista public education was implanted before the Proclamation of the Republic, but was especially after 1910 that this process accelerated, with the creation and regulation of the General Directory of Public Instruction; secondly, it became evident that the administrative/bureaucratic structure instituted by the regulation that created the public offices, strengthened the tendency toward rationalization and bureaucratization of the infra-structure for administering and inspecting Paulista public instruction. This tendency expresses itself in the expansion of the Paulista school apparatus